Fluorescent, Bioluminescent, and Optogenetic Approaches to Study Excitable Physiology in the Single Cardiomyocyte - Broyles, Connor N. (Cells, 2018)
This review briefly summarizes the single cell application of classical chemical dyes used to visualize cardiomyocyte physiology and their undesirable toxicities which have the potential to confound experimental observations. We will discuss, in detail, the more recent iterative development of fluorescent and bioluminescent protein-based indicators and their emerging application to cardiomyocytes. We will discuss the integration of optical control strategies (optogenetics) to augment the standard imaging approach. This will be done in the context of potential applications, and barriers, of these technologies to disease modelling, drug toxicity, and drug discovery efforts at the single-cell scale.